The role of police contact and neighborhood experiences on legal socialization: Longitudinal evidence from adolescents in Brazil. (19th March 2021) - Piccirillo, Debora; García‐Sánchez, Efraín; Chies‐Santos, Mariana; Mizutani Gomes, Aline
ABSTRACT: The legal socialization framework emphasizes the importance of adolescents' encounters with police. We examine how different types of police contact and neighborhood experiences are linked to the legal socialization process among adolescents living in São Paulo, Brazil. Drawing on 669 participants across three waves of panel data from the São Paulo Legal Socialization Study, results from the multilevel longitudinal model revealed that within‐person increases in vicarious police contact were linked to a decrease in police legitimacy over time. Exploratory analyses using a multilevel mediation model indicated that the observed negative effect of vicarious police contact was mediated by evaluations of police procedural justice. As for the between‐person effects, voluntary police contact positively predicted police legitimacy over time. However, the effects of vicarious police contact and violent police contact were mediated by police procedural justice. Additionally, police legitimacy decreased for people who had more exposure to violence and lower levels of fear of crime. The study revealed that the nature of police contact and levels of exposure to violence can have important effects on adolescents' perceptions of police legitimacy, even after accounting for procedural justice.